2017
DOI: 10.1016/j.marpetgeo.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the magnitude of net erosion in the southwest Barents Sea using sonic velocities and compaction trends in shales and sandstones

Abstract: During specific intervals within Mesozoic and Cenozoic times, several areas of the southwestern Barents Sea were subjected to uplift and erosion. Areas with missing shallow stratigraphic interval sections and major erosion can be seen at several places along interpreted regional profiles in the southwestern Barents Sea. A new Normal Compaction Trend (NCT) for two selected shale-and sandstone-dominated lithologies has been constructed based on sonic logs in the southwestern Barents Sea. The shale-dominated NCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Assuming the values proposed by Sclater and Christie (1980), yields a mean value of net erosion of ≈3500 m with a standard deviation of 100 m (Table 3). This is significantly higher than values inferred by compaction studies in this area for the Cenozoic erosional event (1800-2400 m) (Ktenas, Henriksen, Meisingset, Nielsen, & Andreassen, 2017;Ktenas, Meisingset, Henriksen, & Nielsen, 2018). The compaction parameters estimated for the North Sea by Sclater and Christie (1980) are often the default values in basin modelling and for net erosion estimation (Iliffe, Lerche, & DeBuyl, 1992;Nyland, Jensen, Skagen, Skarpnes, & Vorren, 1992;Corcoran & Doré, 2005;Zieba, Daszinnies, Emmel, Lothe, Grover, & Lippard, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Assuming the values proposed by Sclater and Christie (1980), yields a mean value of net erosion of ≈3500 m with a standard deviation of 100 m (Table 3). This is significantly higher than values inferred by compaction studies in this area for the Cenozoic erosional event (1800-2400 m) (Ktenas, Henriksen, Meisingset, Nielsen, & Andreassen, 2017;Ktenas, Meisingset, Henriksen, & Nielsen, 2018). The compaction parameters estimated for the North Sea by Sclater and Christie (1980) are often the default values in basin modelling and for net erosion estimation (Iliffe, Lerche, & DeBuyl, 1992;Nyland, Jensen, Skagen, Skarpnes, & Vorren, 1992;Corcoran & Doré, 2005;Zieba, Daszinnies, Emmel, Lothe, Grover, & Lippard, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…In the Hammerfest Basin, maximum burial is estimated to have been of the order of 900 m deeper than present (Henriksen et al 2011;Ktenas et al 2017). A large part of this erosion can be assumed to be glacial (Elverhøi et al 1998).…”
Section: Abnormally Pressured Formaɵonsmentioning
confidence: 99%
“…Since the area of interest is located at the western edge of the Barents Sea, there is only limited to moderate uplift (0 to 1000 m, Table 1) according to previous studies (e.g. Riis & Fjeldskaar 1992;Ohm et al 2008;Henriksen et al 2011;Baig et al 2016;Ktenas et al 2017). However, the disparity between the uplift values between different studies is noticeable, owing possibly to the various methods employed.…”
Section: Geological Settingmentioning
confidence: 90%
“…However, the disparity between the uplift values between different studies is noticeable, owing possibly to the various methods employed. Ohm et al (2008) and Henriksen et al (2011) suggested no exhumation in the areas of the Senja Ridge and the western margin of Tromsø Basin, whereas, Riis & Fjeldskaar (1992), Baig et al (2016) and Ktenas et al (2017) suggested moderate exhumation (250-1000 m) in these areas ( Fig. 3).…”
Section: Geological Settingmentioning
confidence: 97%